Scollay Square from Hanover Street, ca. 1930 - Unknown (Tufts Archival Research Center, 2005)
Street-level view east-southeast of Scollay Square from Hanover Street. The Crawford House at 17 Court Street is visible in the center of the photograph. The columned north elevation of the City Hall Annex, located on Court Street at Court Square, is visible to the right of Crawford House. Street railroad tracks run down the center of Scollay Square and Court Street, which are also filled with automobiles and pedestrians. Electricity lines and poles, signage and billboards are included in the photograph. 7 15/16 x 9 5/8 Photographs